Monitoring of Potentially Inappropriate Prescriptions in Older Inpatients: A French Multicenter Study. Issue 12 (9th October 2017) - Pandraud‐Riguet, Irène; Bonnet‐Zamponi, Dominique; Bourcier, Elsa; Buyse, Marion; Laribe‐Caget, Sandra; Frémont, Patrick; Pautas, Eric; Verny, Christiane; Hindlet, Patrick; Fernandez, Christine
Abstract : Objectives: To determine whether potentially inappropriate medications (PIMs) or potentially inappropriate associations (PIAs) prescribed knowingly are associated with patient monitoring. Design: Prospective observational study. Setting: Geriatric units (n = 56) in 28 hospitals. Participants: Inpatients aged 75 and older (N = 1, 327). Measurements: Potentially inappropriate prescriptions (PIP) were defined as a PIM or a PIA selected by an expert board from lists of explicit criteria (Beers, Priscus, Laroche, French Health Agency) using a Delphi process. They were considered to be prescribed knowingly if they were maintained after reassessment by the geriatrician and the clinical pharmacist. Primary outcome was the rate of PIPs maintained (prescribed knowingly) and for which a geriatrician declared that specific monitoring was performed. Secondary outcomes were the parameters monitored and the rate of participants receiving knowingly a PIP. Results: One thousand sixty‐three PIPs were detected in 607 participants (46%). After reassessment, 826 (78%) PIPs were maintained in 490 participants (37%), the main reasons being participant's regular treatment and lack of alternative. Psychotropic (36%), cardiovascular (including antithrombotics) (29%), and laxative or antiemetic drugs (16%) were the most‐frequent classes prescribed knowingly. The geriatricians declared to perform clinical or biological monitoring for 69% (n = 570) of PIMs or PIAs prescribed knowingly. Three types of specific monitoring were identified: clinical, biological, and follow‐up with a specialist. Conclusion: Approximately three‐quarters of PIMs or PIAs were prescribed knowingly, of which 69% were monitored, with wide variations in occurrence and in quality according to drug classes. This underlines the need for accurate guidelines on PIP monitoring.